CORRELATING TEACHER SELF-ASSESSMENT SCORE WITH STUDENT ACHIEVEMENT IN ENGLISH AND MATHEMATICS - Muhammad Akram, Sally J. Zepeda (PJE, 2023)
This study aimed to measure the relationship between teacher selfassessment score and student achievement in English and Mathematics. The researchers developed a Self-assessment Instrument for Teacher Evaluation (SITE) based on five National Professional Standards for Teachers developed by the Ministry of Education, Pakistan. Using a convenient sampling method, 279 English or Mathematics teachers of grade 10 in 40 public boys’ and girls’ high schools in district Okara were surveyed who self-evaluated their performance on the SITE II. Additionally, based on the Lahore Board’s annual matriculation examination results 2014, the achievement scores in English or Mathematics (n=7245) of students were also collected from teachers. The study found positive, weak or moderate, relationships between teacher evaluation scores and student achievement in English, as well as in Mathematics. The findings also revealed that Subject Matter Knowledge, Instructional Planning and Strategies, Assessment, Effective Communication, and Continuous Professional Development, individually, significantly predicted student achievement in English and Mathematics. The Subject Matter Knowledge, Instructional Planning and Strategies, and gender significantly explained 28% of the observed variance to predict student achievement in English. Only Subject matter Knowledge explained 12% of the variance in student achievement in mathematics